2022
DOI: 10.3390/su142113894
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Medicinal Mushrooms as Natural Food Dyes and Dye-Sensitised Solar Cells (DSSC): Synergy of Zero Hunger and Affordable Energy for Sustainable Development

Abstract: In 2015, approximately 195 countries agreed with the United Nations that by 2030, they would work to make the world a better place. There would be synergies in accomplishing the 17 Sustainable Development Goals (SDGs). Synergy using a single sustainable resource is critical to assist developing nations in achieving the SDGs as cost-effectively and efficiently possible. To use fungal dye resources, we proposed a combination of the zero hunger and affordable energy goals. Dyes are widely used in high-tech sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 134 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…The combination of mushrooms and wheat in composite flour offers synergistic antioxidant effects (Uriarte-Frías et al, 2021 andAhmad et al, 2022). While wheat contains antioxidants such as phenolic acids and carotenoids, mushrooms boast a diverse range of antioxidant compounds, including betaglucans and ergothioneine (Bell et al, 2022 andKour et al, 2022).…”
Section: Combining Mushrooms and Wheat In Cookie Productionmentioning
confidence: 99%
“…The combination of mushrooms and wheat in composite flour offers synergistic antioxidant effects (Uriarte-Frías et al, 2021 andAhmad et al, 2022). While wheat contains antioxidants such as phenolic acids and carotenoids, mushrooms boast a diverse range of antioxidant compounds, including betaglucans and ergothioneine (Bell et al, 2022 andKour et al, 2022).…”
Section: Combining Mushrooms and Wheat In Cookie Productionmentioning
confidence: 99%
“…21 In order to improve cell efficiency, Pugliese et al 29 demonstrated flexible back-illuminated DSSCs with TiO 2 nanotube photoanodes. Bist et al 30 and Ahmad et al 31 utilized natural extract-mediated and natural food dyes for DSSCs.…”
Section: Introductionmentioning
confidence: 99%